THE ROLE OF LYSYL OXIDASE (LOX) IN PROMOTING CANCER METASTASIS - N. Ab Latif; H.R. Evans; J.T. Erler; A. Gartland (Asian Journal of Medicine & Health Sciences, 2019)
The mechanism of cancer metastasis has been well conceptualized which involves the crosstalk between the primary tumor cells, the premetastatic niche permissive for subsequent tumor cell colonization, cells from the myeloid lineage and even the noncancerous stromal cells within the premetastatic niche. Hypoxia and LOX have been indicated in various studies to have close relationship with numerous malignant cancer cell types and are associated with poor prognosis and low patient survival rate. There is also a distinct connection of hypoxia with increased expression of LOX protein by the primary tumor cells via hypoxia-inducible transcription factor (HIF-1α). Together with other proteins like matrix metalloproteinase-2 and -9 (MMP-2 and MMP-9) and fibronectin (FN), this LOX protein poses a synergistic effect that will promote cancer metastasis. LOX from the primary tumor has been found to migrate to a distant site and initiates matrix remodeling which will result in extracellular matrix (ECM) with high tensile strength conducive for the bone marrow derived cells (BMDCs) to invade. At this new site so called premetastatic niche, there will be a crosstalk between the LOX, FN, MMPs, BMDCs and the stromal fibroblast cells within the surrounding microenvironment. Such crosstalk will cause further invasion by the BMDCs to take place and causes increased matrix remodeling and subsequent matrix degradation, creating a tempting environment for the tumor cells to invade. The BMDCs and stromal fibroblasts will secrete various growth factors which among them is the vascular endothelial growth factor (VEGF), a crucial promoter of angiogenesis. Apart from that, increasing evidence has shown that LOX also conveys its metastatic effect by promoting epithelial-mesenchymal transition (EMT) activities, by intervening the signaling pathways controlling stroma-induced EMT. Angiogenesis and EMT are the two important hallmarks of cancer metastasis which allow the tumor cells to become motile and invasive. Hence, all these factors contribute to the progression of premetastatic niche to become an actual metastases and subsequently acquiring invasive capability and malignancy that allow them to metastasize to other sites.